Prevalence and correlates of psychological distress among retired elite athletes: A systematic review - Mannes, Z. L.; Waxenberg, L. B.; Cottler, L. B.; Perlstein, W. M.; Burrell II, L. E.; Ferguson, E. G.; Edwards, M. E.; Ennis, N. (International Review of Sport and Exercise Psychology, 2019)
This article presents results of a systematic review of the literature (2000-2017) examining the prevalence and correlates of psychological distress among retired elite athletes. Forty articles were selected and included. Our review suggests the prevalence of psychological distress among retired athletes is similar to that found in the general population. However, subgroups reporting medical comorbidities, significant pain, a greater number of concussions, less social support, and adverse psychosocial factors were at greater risk for psychological distress. Additionally, athletes experiencing psychological distress in retirement often do not seek treatment for their distress. Based on the existing literature, there is a need for greater standardization and use of reliable measures, as well as use of diagnostic interviews in order to assess the most accurate prevalence of psychological distress among these athletes. Longitudinal designs, matched control groups, more heterogeneous samples, and use of multivariate analyses would also help to more accurately determine the prevalence and risk factors of psychological distress in this population. This review suggests a number of different clinical implications and highlights directions for future research to enhance our understanding of the long-term psychological health of former elite athletes.